How much platinum is enough? Stability of Pt-coated titanium films for porous transport layers (PTLs) in acidic and fluoride-containing electrolyte - da Silva, Gabriel C.; Xie, Xianxian; Vorochta, Michael; Khalakhan, Ivan; Cherevko, Serhiy (Electrochimica Acta, 2026)
Platinum-coated titanium porous transport layers (PTLs) are commonly used in proton exchange membrane water electrolyzers (PEMWE) to ensure electrical contact and corrosion resistance on the anode side. While the impact of platinum on interfacial performance has been extensively studied, the effect of Pt coating thickness on dissolution stability is still not well understood. In this study, model Pt/Ti thin films with tuned Pt thicknesses ranging from 1 to 100 nm are fabricated using magnetron sputtering. The films are examined using operando scanning flow cell inductively coupled plasma mass spectrometry (SFC-ICP-MS). Our findings reveal that thin Pt coatings do not block Ti dissolution under the tested conditions, while coatings of 20 nm or thicker substantially suppress Ti dissolution under specific dynamic operating protocols. In fluoride-containing electrolytes, the most robust and consistent suppression of Ti dissolution across all investigated conditions is achieved with 100 nm Pt coating. These results highlight critical Pt thickness thresholds necessary to suppress Ti corrosion under the operating conditions investigated here and provide a mechanistic foundation for the rational design of PTL coatings prior to validation at the device level.
CRIS-Team Scopus Importer:2026-02-20
Keywords: Metal dissolution; Platinum coating thickness; Porous transport layers; Proton exchange membrane water electrolysis; Pt/Ti model films